Advances and Challenges in Diagnostics of Toxoplasmosis in HIV-Infected Patients - Roland Wesołowski; Marta Pawłowska; Małgorzata Smoguła; Karolina Szewczyk-Golec (Pathogens, 2023)
Toxoplasma gondii is a worldwide distributed protozoan parasite. This apicomplexan parasite infects one-third of the population worldwide, causing toxoplasmosis, considered one of the neglected parasitic infections. In healthy humans, most infections are asymptomatic. However, in immunocompromised patients, the course of the disease can be life-threatening. Human immunodeficiency virus (HIV)-infected patients have a very high burden of Toxoplasma gondii co-infection. Thus, it is essential to use modern, sensitive, and specific methods to properly monitor the course of toxoplasmosis in immunodeficient patients.